Effects of 21st‐century climate, land use, and disturbances on ecosystem carbon balance in California. (24th June 2019) - Sleeter, Benjamin M.; Marvin, David C.; Cameron, D. Richard; Selmants, Paul C.; Westerling, A.LeRoy; Kreitler, Jason; Daniel, Colin J.; Liu, Jinxun; Wilson, Tamara S.
Abstract: Terrestrial ecosystems are an important sink for atmospheric carbon dioxide (CO2 ), sequestering 30% of annual anthropogenic emissions and slowing the rise of atmospheric CO2 . However, the future direction and magnitude of the land sink is highly uncertain. We examined how historical and projected changes in climate, land use, and ecosystem disturbances affect the carbon balance of terrestrial ecosystems in California over the period 2001–2100. We modeled 32 unique scenarios, spanning 4 land use and 2 radiative forcing scenarios as simulated by four global climate models. Between 2001 and 2015, carbon storage in California's terrestrial ecosystems declined by −188.4 Tg C, with a mean annual flux ranging from a source of −89.8 Tg C/year to a sink of 60.1 Tg C/year. The large variability in the magnitude of the state's carbon source/sink was primarily attributable to interannual variability in weather and climate, which affected the rate of carbon uptake in vegetation and the rate of ecosystem respiration. Under nearly all future scenarios, carbon storage in terrestrial ecosystems was projected to decline, with an average loss of −9.4% (−432.3 Tg C) by the year 2100 from current stocks. However, uncertainty in the magnitude of carbon loss was high, with individual scenario projections ranging from −916.2 to 121.2 Tg C and was largely driven by differences in future climate conditions projected by climate models. Moving from a high to a low radiative forcing scenario reduced net ecosystem carbon loss by 21% and when combined with reductions in land‐use change (i.e., moving from a high to a low land‐use scenario), net carbon losses were reduced by 55% on average. However, reconciling large uncertainties associated with the effect of increasing atmospheric CO2 is needed to better constrain models used to establish baseline conditions from which ecosystem‐based climate mitigation strategies can be evaluated. Abstract : Terrestrial ecosystems are an important sink for atmospheric carbon dioxide (CO2 ). However, the future direction and magnitude of the land sink is highly uncertain. For the state of California, we modeled 32 unique scenarios, spanning 4 land use and 2 radiative forcing scenarios as simulated by four global climate models. Under nearly all future scenarios, carbon storage in terrestrial ecosystems was projected to decline, with an average loss of −9.4% (−432.3 Tg C) by the year 2100. However, uncertainty in the magnitude of carbon loss was high, and was largely driven by differences in future climate conditions projected by climate models.